An analysis of the causes and consequences of conflict and violence in A.C. Jordan's The Wrath of the Ancestors and R.L. Peteni's Hill of Fools - Yola, Ziyanda (School of Languages and Literatures, 2017)
South Africa is one of the countries with high rates of violence in the world. The beginning of high rates of conflict and violence in South Africa can be traced as far back as the 17th century. During this era seven wars were fought in this country. The apartheid that was later experienced in South Africa also contributed to South Africa's high rates of violence. Violence is still a prominent issue in this country. In 2012 violence occurred in Lonmin Platinum mine in Marikana and in 2015 foreign nationals also experienced violence in South Africa. Morovere, the rates of violence against women and children remain high even after all the awareness and efforts to reduce it. This thesis deals with the causes of conflict and violence in South Africa particularly and in Africa in general. This is done by analyzing The wrath of the ancestors by A.C Jordan and Hill of fools by R.L Peteni as a case study. The two selected novels are going to be analysed using quantitative research methodology. The study maintains that literature is a reflection of reality and therefore the conflict and violence in the two novels is treated as a true reflection of conflict and violence in South Africa.